COLLECTIVE SPIRIT - Cavling, Viggo, 1887-1946. Link ([S.l.])
1 online resource
Keywords: The Collective Spirit (1925) lays down a rough outline of what science can tell us as to the progress of evolution, and criticises the various interpretations, before endeavouring to formulate an idealist theory of evolution.